Effect of Temperature, Concentration and Contact Time of Sodium Hypochlorite on the Treatment and Revitalization of Oral Biofilms - Aldo del Carpio-Perochena; Clovis Monteiro Bramante; Marco Hungaro Duarte; Flaviana Bombarda de Andrade; Marcia Zardin Graeff; Marina Marciano da Silva; Bruno Cavalini Cavenago; Samuel Lucas Fernandes (Tabriz University of Medical Sciences, 2015)
Background and aims. Increasing the temperature of sodium hypochlorite (NaOCl) enhances its dissolution and antibacterial properties. However, the high resistance of multi-species biofilms could restrict the effect of the solution regardless of its temperature, enabling the long-term recovery of the surviving bacteria. The aim of this study was to investigate if the increase of temperature of NaOCl improves its antibacterial and dissolution ability on oral biofilms and if the post-treatment remaining bacteria were capable of growing in a nutrient-rich medium. Materials and methods. Forty dentin blocks were infected intra-orally for 48 hours. Then, the specimens were treated with 1% and 2.5% NaOCl at room temperature (22ºC) and body temperature (37ºC) for 5 and 20 min. The percentage of live cells and the biovolume were measured pre- (control) and post-treatment and after the biofilm revitalization. Four confocal 'stacks' were chosen from random areas of each sample. Statistical analysis was performed using Kruskal-Wallis and Dunn tests. Statistical significance was defined at P <0.05. Results. All the NaOCl groups were effective in dissolving the biofilm at any temperature, concentration and contact time without statistical differences among them (P >0.05). The 1%-NaOCl for 5min was not able to significantly kill the bacteria, regardless of its temperature and contact time (P >0.05). Conclusion. The temperature variation of the NaOCl was not relevant in killing or dissolving bacterial biofilms. Twenty-four hours of reactivation did not appear to be enough time to induce a significant bacterial growth.